A case study assembling of hand tractor by Separa Enterprises - Badeo, Luz Cervantes; Lagman, Myrna V. (Tacloban City Management and Technology Program, University of the Philippines College Tacloban, 1980)
This study evaluated Separa Enterprises's operations in the assembly of hand tractors, identified existing problems, and indicated their relative priority for finding solutions through personal interviews.
Thesis (Bachelor of Science in Agri-business) -- University of the Philippines College Tacloban, March 1980.
Keywords: Separa Enterprises; Hand tractors assembly -- Region 8.; Plant assembly -- Management